A study of farm input supply in the West Gonja District: implications for smallholder development - Dosoo, Ebenezer (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Development Planning and Management.